A Microbiology Module Development on Antagonism Between Fungi and Bacteria Based on Problem-Based Learning to Improve Student’s Critical Thinking Skills - Maknuna, Durrotul; Hastuti, Utami Sri; Prabaningtyas, Sitoresmi (BIOEDUKASI, 2024)
The purpose of the research is to develop Microbiology Module on the topic "The Antagonism of P. chrysogenum against Escherichia coli, Staphylococcus aureus, and Bacillus subtilis" that have criteria valid, practice, and effective for improve the student’s critical thinking skills. This research type is a quasi-experiment research using a non-randomized pretest-posttest control group design. The learning model uses the ADDIE approach which is implemented with the Problem Based Learning (PBL) model. Data collection uses response questionnaires, pretest and post-test, and validation sheets. The effectiveness of the Microbiology Module in improving students' critical thinking skills can be known through the pretest and post-test scores analyzed through the One Way Ancova test. The research and development result proved that the validation score gives by media and teaching materials experts was 99%, material experts were 98%, and Biology education practitioners were 100% from the student responses were 93%. The p-level results showed 0.00<0.05, so the modules were effective to use in the learning process. The research results proved that a significant difference between the experimental class learned using the Microbiology Module compared to the control class PowerPoint without the Microbiology Module. The modules is valid, practical, and effective to use in improve the student’s critical thinking skills.